The Administrative Use of Law in China: The Baori Golf Club Tax Case - Jiang, Zhaodong (Columbia Journal of Asian Law, 1998)
On August 18, 1997, the Shenzhen Local Taxation Bureau (the “Local Taxation Bureau”) auctioned off assets of the Baori Golf Club, a Chinese-Japanese joint venture (“Baori” or the “JV”). Out of the 260 million yuan auction proceeds, 103 million yuan went to the state treasury to satisfy the government’s tax claims against the JV. The Baori Golf Club tax case is significant in several respects. As Baori Golf Club involved over 147 million yuan tax-related claims and penalties, the case ranks among the top tax cases in China’s history. In an unprecedented move, the Chinese authorities openly charged the JV and its Japanese management with toushui or “tax evasion” and kangshui or “refusal to pay tax”, each charge carrying severe administrative and criminal penalties under Chinese legislation. It was the first time the offense ofkangshui had been publicly levelled against a foreign investment enterprise since the country’s opening up in the late 1970s. How did the Chinese authorities explain this extraordinary case? According to the Director of the Local Taxation Bureau, the local tax officials merely “administered tax according to law” (yifazhishui). The Local Taxation Bureau’s decision against the JV was indeed replete with citations of legislation, government regulations and ministerial pronouncements. Other official accounts of the case made repeated references to law. What is the significance of the slogan “administering tax according to law”? In China, top officials in the executive branch ofthe Chinese government wield broad law-making powers. They may interpret and implement legislation by promulgating regulations and rules of their own. Such administrative regulations and rules are not reviewable in court. In contrast, Chinese court judges are better described as “adjudication functionaries” and their powers are limited to adjudicating the types of cases as prescribed by legislation. As far as tax law is concerned, while the court is given a role in settling disputes between the authorities and taxpayers, few tax cases have ended up in the courtroom. For many Chinese citizens and businesses, taking tax officials to court can be a risky move and an unrewarding experience. Furthermore, access to court is hampered by technical hurdles and court judges are subject to the political influence of local and central administrative officials. Not surprisingly, the attempts of the Japanese investor in Baori to challenge the Local Taxation Bureau’s decisions and action in court failed. Like most other tax cases in China, Baori remains an administrative case (xingzheng anjian). In contrast to a judicial case (sifa anjian) where the court makes a pronouncement on the dispute between the authorities and the taxpayer, the decision of tax officials in a tax administrative case authoritatively disposes of substantive issues without court involvement. Although it is generally known that administrative officials play a pivotal role in law making and interpretation in China, little attention has been devoted to how law has actually been used in an administrative case. This Article attempts to shed light on that issue through an investigation into how the local tax officials used law while handling the Baori case and also develops a trilogy of law use in Chinese administrative cases.